2022
DOI: 10.1155/2022/8562390
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the Multiattribute Decision-Making for the Development of the Tourism Industry Using Complex Intuitionistic Fuzzy Hamy Mean Operators

Abstract: In the aggregation of uncertain information, it is very important to consider the interrelationship of the input information. Hamy mean (HM) is one of the fine tools to deal with such scenarios. This paper aims to extend the idea of the HM operator and dual HM (DHM) operator in the framework of complex intuitionistic fuzzy sets (CIFSs). The main benefit of using the frame of complex intuitionistic fuzzy CIF information is that it handles two possibilities of the truth degree (TD) and falsity degree (FD) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 53 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Hussain et al. ( 2022a ) utilized the IF Hamy mean operators in the assessment of tourism industry development.…”
Section: A Systematic Review Of Ifssmentioning
confidence: 99%
“…Hussain et al. ( 2022a ) utilized the IF Hamy mean operators in the assessment of tourism industry development.…”
Section: A Systematic Review Of Ifssmentioning
confidence: 99%
“…Ullah [ 22 ] characterized some new approaches to PFSs by exploring the theory of symmetric mean aggregation operators. Hussain et al [ 23 ] determined the correlation among input arguments based on complex IFSs and established a MADM problem to assess a suitable tourism industry. Riaz and Farid [ 24 ] expressed the superiority of the PFSs and investigated some new approaches to complete the selection process under the third party of the linguistic provider.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing social trust propagation is another strategy for solving the decision-making problem that Liu et al [ 20 ] demonstrated. Hussain et al [ 21 ] grouped different tourist spots and devised an excellent structure for boosting the economy of any area. Biswas and Deb [ 22 ] applied the basic ideas of PyF information to show how reliable Schweizer Sklar aggregation operators are.…”
Section: Introductionmentioning
confidence: 99%